Evaluation of dairy calves performance and welfare kept on different facilities and consuming different sources of roughage (Research, Society and Development, 2021)
The study had as objective evaluate dairy calves welfare housed in different facilities, kept confined or in individual hutches, receiving alfalfa hay or sorghum silage, as roughage. Eight animals were used, being four Holsteins and four crossbreed, which six were males and two were females, randomly distributed by birth order and arrival to the following treatments: AF – individual hatches + alfalfa hay; AS – individual hatches + sorghum silage; BF – conventional calf housing + alfalfa hay; BS – conventional calf housing + sorghum silage. Calves from different treatments had similar behavior spending time with activities as idle, rumination, visits to troughs of concentrate and roughage and sucking. Animals kept in AS treatment were more often the water cooler when compared to animals of other treatments. The respiratory frequency of calves from AF treatment was higher when compared to animals from BF and BS treatments; however this difference wasn’t observed when it was compared to animals from AS treatment. The facilities and roughage source doesn’t interfere with feeding behavior. Newly installed animals remain more time in idleness standing and less time with rumination. Dairy calves kept in individual hatches enhance heat loss as the increase of respiratory frequency.